Factual Survey of Junior Technical Schools New Dekhi October, 1964 - Planning Commission (Planning Commission, Government of India, 1964)
The Planning Commission of India conducted a comprehensive survey of Junior Technical Schools (JTS) in preparation for the Fourth Five Year Plan (1964–1969) to evaluate their effectiveness in providing vocational education aligned with economic development and workforce needs. The survey revealed significant challenges, including high dropout rates, underutilization of resources, and limited transition into industrial employment, with only 36% of enrolled students completing the three-year course and merely 18% entering the industrial workforce. Wastage of facilities was notably high at 64.5%, primarily due to student dropouts, highlighting the urgent need for strategic reforms. The survey also indicated that nearly 38% of admitted students scored below 40% in qualifying examinations, raising concerns regarding the academic preparedness of entrants and the quality of education delivered. Recommendations emphasized stronger linkages with higher education by recognizing JTS certificates for polytechnic and pre-university admissions, curriculum reforms to balance academic and vocational training, measures to incentivize academic performance, and the standardization of practices to address inter-state variability in outcomes. The findings underscore the critical need to enhance the efficacy of JTS, reduce educational wastage, and ensure that these institutions function effectively as gateways to technical education and as bridges to industrial employment, thereby informing policy decisions for the Fourth Plan and contributing to India’s broader educational and economic objectives.
Planning Commission (Education Division)
Keywords: Junior Technical Schools; Planning Commission; Fourth Five Year Plan; Vocational Education; Student Retention; Curriculum Reform; Industrial Employment; Polytechnics; Educational Wastage; Academic Performance; Inter-State Variability; Resource Utilization